THE USE OF PHRASES IN ABDULLA QAHHOR'S STORIES AND ABDULLA ORIPOV'S POEMS (Intent Research Scientific Journal, 2023)
In this article, the linguistic and cultural features of phrases in the work of master of words Abdulla Qahhor and how they are gaining meaning are revealed as examples. How phrases are used in the lyrics of our Uzbek national poet Abdulla Oripov is explained through fragments.